Quality control of three BrightView XCT gamma chambers in the first six months of operation (Revista de Física Médica, 2013)
This study sought to compare the behaviour of the three gamma chambers of the Nuclear Medicine Department of La Fe Hospital. For this, we perform a series of periodic measurements of the two most important subsystems in the operation of the equipment, the nuclear medicine imaging acquisition system, SPECT, and X-ray imaging system for tomography, XCT. The study had an acquisition time of the first six months of operation of the gamma cameras.It is noted that the three gamma chambers have particular behaviours, being the time required between calibrations for both subsystems entirely individual. In addition, there was a large variability among the periods of the different calibrations, depending on the type of calibration performed by the Philips Technical Service.